Pengaruh Kecepatan Dan Waktu Pengadukan Dalam Pengolahan Air Gambut Menggunakan Serbuk Biji Asam Jawa (Tamarindus Indica L) Sebagai Biokoagulan - Asward, Mayshara; Elystia, Shinta; Yenie, Elvi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Peat water has potential as a source of raw water because of its considerable availability, but the characteristics of peat water have not standard of quality according to Permenkes No.416/MENKES/PER/IX/1990 and PP. 82 of 2001. One method of peat water treatment is coagulation flocculation that requires coagulant. Tamarind seed powder is one type of natural coagulant substitute chemical coagulant because it contains tannin, natural polymer such as starch, sap, and albuminoid that play a role in water purification. This research used coagulation and flocculation method with combination of stirring variation 100 rpm / 40 rpm; 125 rpm/45 rpm; 150 rpm/50 rpm and 10 minutes flocculation time; 20 minutes; 30 minutes using Tamarind seed powder with 200 mesh particle size and dose 2,5 gr/200 mL peat water to the decrease COD, dyestuff, organic matter, TSS, and pH. In this study also conducted pH conditioning at peat water pH and pH condition 7. The results showed that peat water treatment at fast rapping speed 125 rpm, slow stirring speed 45 rpm and slow stirring time 20 minutes at natural pH condition of peat water (4,69) using Tamarind seed powder have the best effect on water quality parameter and able to increase water pH. Decrease in COD by 75.90%; dye of 84.59%; organic matter 72,12%; and TSS of 81.70% and peak water pH to 6,8. Keywords : Coagulation Flocculation, Peat Water, Stirring Times, Flocculation Times, Tamarind Seed Powder